2015
DOI: 10.3390/su7055371
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Arable Land Demand for Food in India and China: A Potential Threat to Food Security

Abstract: India and China are two similar developing countries with huge populations, rapid economic growth and limited natural resources, therefore facing the massive pressure of ensuring food security. In this paper, we will discuss the food security situations in these two countries by studying the historical changes of food supply-demand balance with the concept of agricultural land requirements for food (LRF) from 1963-2009. LRF of a country is a function of population, per capita consumption/diet, cropping yield a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Specifically, reduction in grain purchase price, encouragement of agricultural structural adjustment (i.e., promotion of cash crops in lieu of grain), and promotion of ecological projects (i.e., the "grain for green" program) were the most decisive measures at that time [31]. Meanwhile, the rapid industrialization and urbanization in China along with a steep decline in the net revenue from grain farming constituted important factors for land conversion to non-agricultural use and decrease in agricultural inputs for grain production [32].…”
Section: Period-wise Analysismentioning
confidence: 99%
“…Specifically, reduction in grain purchase price, encouragement of agricultural structural adjustment (i.e., promotion of cash crops in lieu of grain), and promotion of ecological projects (i.e., the "grain for green" program) were the most decisive measures at that time [31]. Meanwhile, the rapid industrialization and urbanization in China along with a steep decline in the net revenue from grain farming constituted important factors for land conversion to non-agricultural use and decrease in agricultural inputs for grain production [32].…”
Section: Period-wise Analysismentioning
confidence: 99%
“…The increased demand for food, fiber and fuel products has led to a rapid change in land use and to the progressive transformation of traditional agronomic techniques into high-input methods of land-resource exploitation [2,3], with a negative impact on non-renewable natural resources such as soil [4][5][6]. Since the industrial age, increasing pressure on crop production has been observed in developed countries with implications for the ecological sustainability of agricultural systems and the quality of the environment [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Arable lands are the type of lands capable to be ploughed and therefore are critical for grain production [1]. Thus, maintaining a certain extent of arable land is the basis and guarantee for food security in many countries.…”
Section: Introductionmentioning
confidence: 99%